The Effect of Extensive Hydrolyzate Formula on the Growth and Development of Infants With Cow's Milk Allergy - Nuraeni Salsabila, Irma; Purnomosari, Lupi (Ridwan Institute, 2024)
Cow's milk allergy is a common condition in babies and children. Allergic reactions can occur when the body reacts to the proteins in cow's milk, causing various symptoms such as skin rashes, vomiting, diarrhea, or even more serious reactions. Babies who suffer from cow's milk allergy need appropriate treatment so that their growth and development is not disrupted. One approach used in managing cow's milk allergy is to provide an extensive hydrolyzate formula. The aim of this study was to evaluate the effect of providing extensive hydrolyzed formula on the growth and development of babies suffering from cow's milk allergy. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study concluded that the use of extensive hydrolyzed formula is an effective choice for babies who are allergic to cow's milk. This research shows that this formula has a positive impact on the baby's weight growth according to his age. However, in terms of infant development, there is no significant difference in the effect between the use of extensive hydrolyzed formula and soy protein isolate on various aspects, including global development, gross motor skills, fine motor skills, language and social personality in children who are allergic to cow's milk